PENGARUH AUDIT DELAY PADA INSTANSI PEMERINTAH DAERAH SUBOSUKOWONOSRATEN TAHUN 2009-2014 - Endang Purwaningsih; Angelina Hapsari (Media Akuntansi, 2018)
The research to examine the influence factors that affect audit delay in Subosukawonosraten local government. The purpose in this research to determine the influence factors that affect audit delay in Subosukawonosraten local government. Used a sample of 38 financial statements were derived from the seven districts Subosukawonosraten and  taken from Badan Pemeriksa Keuangan (BPK). The dependent variable of this study is the audit delay. While the independent variable of this research is the complexity of the field SKPD, the auditor's opinion, the budget absorption, and the the level of wealth. Sampling using purposive sampling method and using multiple linear regression analysis. Results shows that the budget absorption has a significant positive influence on audit delay. While the complexity of the field SKPD, the auditor's opinion, and the level of wealth has no effect on audit delay.